Evaluation of Antibiotic Utilization Patterns and Therapeutic Indicators in a Pediatric Tertiary Care Inpatient Department: Research Article (Journal of Pharma Insights and Research, 2026)
Antimicrobial stewardship in pediatric populations is essential to reduce the progression of multidrug-resistant organisms and ensure the efficacy of life-saving therapies. Rational prescribing remains a challenge in hospitals where infectious diseases account for a high percentage of hospital admissions. Analysis of inpatient data from a tertiary care teaching hospital indicates that respiratory tract infections serve as the primary clinical indication for antibiotic initiation. Among the various classes of antimicrobials, third-generation cephalosporins, specifically ceftriaxone, are utilized with the highest frequency, often administered via the intravenous route. Observations of prescribing habits reveal a significant reliance on injectable formulations and a prevalent trend toward polypharmacy, with a substantial number of patients receiving more than six medications concurrently. While adherence to the National List of Essential Medicines and generic naming conventions is evident, the frequent use of broad-spectrum agents in an empirical capacity highlights a critical area for intervention. Implementation of structured antimicrobial stewardship programs, guided by periodic prescription audits and local sensitivity data, is necessary to optimize therapeutic outcomes. Improving the rational use of antibiotics through early intravenous-to-oral switch therapy and targeted narrow-spectrum selection can significantly reduce the risk of adverse drug reactions and healthcare-associated costs. Continuous monitoring of these patterns serves as a foundation for developing evidence-based guidelines tailored to the unique physiological requirements of the pediatric demographics